2003
DOI: 10.1097/00005344-200301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of K+ Channels to Relaxation Induced by 17β-Estradiol but Not by Progesterone in Isolated Rat Mesenteric Artery Rings

Abstract: 17beta-Estradiol and progesterone were found to relax various vascular beds through multiple mechanisms. However, the exact ionic mechanisms underlying the acute relaxant responses to both hormones are incompletely understood. This study was aimed to examine the possible role of K channel activation in the relaxation induced by both hormones in isolated rat mesenteric artery rings. Isometric tension of each ring was measured with Grass force displacement transducers. In rat endothelium-denuded rings preconstri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, acute treatment with higher concentrations (Ն10 Ϫ6 mol/L) of E 2 reduces agonist-induced vasocontractions. 32 Thus, acute and nongenomic effects of estrogen and tamoxifen may differ from their long-term and genomic effects on vascular motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, acute treatment with higher concentrations (Ն10 Ϫ6 mol/L) of E 2 reduces agonist-induced vasocontractions. 32 Thus, acute and nongenomic effects of estrogen and tamoxifen may differ from their long-term and genomic effects on vascular motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors observed that environmental estrogenic pollutants and βES induced a rapid and endothelium-independent relaxation by inhibiting LTCC in vascular smooth muscle cells [27] . Activation of K + channels by PRG and by βES in vascular smooth muscle may induce repolarization of plasma membrane, which will close the VOCCs and contribute to the vascular relaxation [27][28][29][30] . This mechanism does not appear to be very important for PRG [29] , but the opening of Ca 2+ -activated K + (BK Ca ) channels by βES has been observed in human coronary artery smooth muscle cells [30] and rat aorta A7r5 cells [27] .…”
Section: Centro De Investigação Em Ciências Da Saúde Universidade Damentioning
confidence: 99%
“…The K v channel blocker 3,4-diaminopyridine (3,4-DAP) 13 at 1 mmol/L had similar effects (nϭ5, Figure 3B and Figure IIB). The small-conductance, Ca 2ϩ -activated K ϩ channel blocker apamin 4 (1 mol/L, nϭ6; Figure 4A and Figure IIC) and the K ATP channel blocker glibenclamide 10,14 (3 mol/L, nϭ8; Figure 4B and Figure IID) were not effective. The inward rectifier K ϩ channel blocker Ba Figure IVB), and tetrapentylammonium, 17 which also blocks K ATP channels, 18 (2 mol/L, nϭ6, not shown) enhanced serotonin-dependent contractions by 20% to 30% in both (Ϫ) fat and (ϩ) fat rings.…”
Section: Role Of K V Channelsmentioning
confidence: 99%
“…The rings were placed in a small vessel wire myograph under an optimal resting tension of 2 mN. 3,4 Tension is expressed as a percentage of the steady-state tension (100%) obtained with isotonic external 60 mmol/L KCl.In the first series of experiments, the rings were exposed to increasing doses of serotonin (10 Ϫ8 to 10 Ϫ5 mol/L), endothelin I (10 …”
mentioning
confidence: 99%
See 1 more Smart Citation